A historic turning point. Political change and the socio-institutional situation in Latin America - Fernando Calderon G. (CEPAL Review, 2008)
Latin America is going through a time of political crisis, reconfiguration and change in which the relationship between institutions and equity will be crucial to future democratic governance. In particular, this crisis and this reconfiguration are first and foremost sociocultural in nature. Politics and political actors would be in no position to resolve politico-institutional problems if they were not capable of confronting society’s problems, particularly those of equity and poverty. This article synthesizes and reviews a number of socio-historical trends, formulates some observations aimed at illustrating and disaggregating its main findings, considers the medium-term outlook and suggests a road map for improving democratic governance in Latin America.